The role of perceived organisational support and leader humor in participative leadership and innovative work behaviour in small firms - Fatoki, Olawale (International Journal of Management and Sustainability, 2023)
The objective of this study was to investigate the impact of participatory leadership on the work behaviour of employees in small enterprises, specifically focusing on their level of innovation. Furthermore, the present study sought to examine the mediating effect of perceived organizational support and the moderating effect of leader humor. The study utilized a quantitative research design. The researchers utilized a cross-sectional survey methodology in order to collect data. The study utilized a non-probability sampling methodology. Small-scale business employees made up the study's participants. The hypotheses of the study were tested using the Partial Least Square Structural Equation modelling (PLS SEM). The findings indicated that participative leadership is positively related to employee IWB. The mediating effect of perceived organizational support in the relationship between participative leadership and innovative work behaviour is significant. The study's theoretical implication is around the development of a model that illustrates the impact of perceived organizational support and leader humor on the connection between participative leadership and employee innovative work behaviour. The study's findings contribute to the comprehension of the various aspects that can impact the association between participatory leadership and innovative work behaviour exhibited by employees. Practical implications include the attendance of training on leadership and innovation by owners/managers and employees of small firms.